Histone chaperone CAF‐1 promotes HIV‐1 latency by leading the formation of phase‐separated suppressive nuclear bodies. (19th March 2021) - Ma, Xiancai; Chen, Tao; Peng, Zhilin; Wang, Ziwen; Liu, Jun; Yang, Tao; Wu, Liyang; Liu, Guangyan; Zhou, Mo; Tong, Muye; Guan, Yuanjun; Zhang, Xu; et al.
Abstract: HIV‐1 latency is a major obstacle to achieving a functional cure for AIDS. Reactivation of HIV‐1‐infected cells followed by their elimination via immune surveillance is one proposed strategy for eradicating the viral reservoir. However, current latency‐reversing agents (LRAs) show high toxicity and low efficiency, and new targets are needed to develop more promising LRAs. Here, we found that the histone chaperone CAF‐1 (chromatin assembly factor 1) is enriched on the HIV‐1 long terminal repeat (LTR) and forms nuclear bodies with liquid–liquid phase separation (LLPS) properties. CAF‐1 recruits epigenetic modifiers and histone chaperones to the nuclear bodies to establish and maintain HIV‐1 latency in different latency models and primary CD4 + T cells. Three disordered regions of the CHAF1A subunit are important for phase‐separated CAF‐1 nuclear body formation and play a key role in maintaining HIV‐1 latency. Disruption of phase‐separated CAF‐1 bodies could be a potential strategy to reactivate latent HIV‐1. Synopsis: One major obstacle to achieving a functional cure of AIDS is HIV‐1 latency. Multi‐omics screening and physicochemical assays reveal that phased‐separated CAF‐1 nuclear bodies is a core factor contributing to HIV‐1 latency. The histone chaperone CAF‐1 contributes to HIV‐1 latency in different latency models and primary CD4 + T cells. Epigenetic modifiers and histone chaperones are recruited by CAF‐1 to nuclear bodies. CAF‐1 bodies are phase‐separated hetero‐condensates. Phase separation properties of CAF‐1 play a key in maintaining HIV‐1 latency. Abstract : Enrichment of histone chaperone CAF‐1 on long terminal repeats of integrated HIV‐1 retrovirus recruits epigenetic and chromatin modifiers involved in viral latency via liquid‐liquid phase separation.